Improving access to phosphorus- and sodium-restricted foods for people living with chronic kidney disease in remote First Nations - Rebecca Schiff; Holly Freill (James Cook University, 2020)
Context: Food insecurity in northern, remote Canadian communities has become increasingly recognised as a significant issue in rural health research and policy. Over the past decade, numerous government and academic reports have emerged, documenting the severity of this issue for the health people living in the Canadian north. People living in northern and remote Canadian communities experience significant challenges related to the cost, quality, and variety of market (store-bought) foods. These issues may be of particular concern for those living with chronic diseases that require therapeutic diets, such as chronic kidney disease (CKD). Issues: There is little to no research that documents the impact of food insecurity on disease management and quality of life for those living with CKD and end-stage renal disease (ESRD). There is also limited literature on food access for people living with ESRD in northern and remote communities. People living with food insecurity and CKD in remote communities might experience significant challenges in accessing the foods necessary for adhering to dietary guidelines. Lessons learned: This commentary examines northern food insecurity and draws attention to dietary challenges for residents of remote communities who are living on restricted or therapeutic diets due to chronic disease. In particular we point to the needs of those living with late-stage CKD and ESRD. We call attention to the need for clinicians to understand the capacity of patients to adhere to therapeutic dietary guidelines in remote communities.